The Decision Support System for Cashier Recruitment Implements the Multi-Attribute Utility Theory Method - Lubis, Juanda Hakim; Mesran, Mesran; Siregar, Cindy Astika (Forum Kerjasama Pendidikan Tinggi, 2024)
CV.Sumber Segar Lestari is a five-star supermarket that serves the best products on the market, namely imported products. High quality human resources are very necessary to improve a company. In searching for quality human resources according to the company's needs, CV.Sumber Segar Lestari is still carried out manually, namely the cashier reception process at CV.Sumber Segar Lestari (Brastagi Supermarket) uses a cashier reception system based on the Company's Operational Standards guidelines. Starting from the cashier acceptance process by selecting each incoming job application. Then the process of evaluating prospective cashier employees is carried out, including: examining applications and required documents, conducting written tests, interviews, and deciding whether to accept or reject the prospective cashier employee. This method of assessment takes a long time and is prone to errors. Especially if many applicants submit applications. In addition, the assessment process and results can only be seen by personnel, it is very possible to manipulate test results. To solve this problem, this research uses the Multi Attribute Utility Theory method. The Multi Attribute Utility Theory method is a quantitative comparison method that usually combines measurements of different risk costs and benefits. The Multi Attribute Utility Theory method is used to provide an assessment and consideration of the best alternative from various existing options. Processing values using the death method will produce rankings. The final result obtained was alternative A3 which had the highest final score of 0.595 in the name of Mulia Dinda Ramadani